“French-English Translation in Canada” by Maynard Gertler: Edited and with an introduction by Ruth Panofsky - Panofsky, Ruth (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2020)
“French-English Translation in Canada” is the transcript of a talk given by Montreal publisher Maynard Gertler to an unidentified audience in 1976. When Gertler founded Harvest House in 1959, his aim was to issue the first English-language translations of the works of Québécois writers in inexpensive, accessible editions. The talk is a document of enduring value that provides incisive analysis of contemporary Canadian publishing and presents the challenges facing a domestic publisher who was committed to issuing French works in English translation.